Strengthening the Nexus: Policy and Legislative Reforms for University-Industry Collaboration in Kazakhstan - YESSIMOVA, Sholpan; RAKHYMZHANOV, Yerkesh; SPANOVA, Bagdat; BAIZHANOVA, Sulushash; SEIDAKHMETOV, Marat; YESSENOVA, Aiman; ALTYNBASSOV, Bakhyt (Theoretical and Practical Research in Economic Fields, 2024)
The aim of this study is to examine the synergistic benefits that arise from collaborations between universities and industrial companies, examining the mutual advantages that both entities have. This research evaluates the government's efforts to cultivate such partnerships through a comprehensive documentary analysis of current policy documents and legislation. The findings indicate that a recently established ministry in Kazakhstan is actively developing proposals for legislative amendments to enhance the framework for collaboration between universities and industry. It is noteworthy that the government is providing tax preferences and incentives to industrial entities that collaborate with academic institutions, with the expectation that these measures will lead to beneficial outcomes. Despite these positive measures, the study revealed significant obstacles that prevent effective collaboration, such as legislative gaps and a general apprehension among industrial companies to set partnerships, due to the ineffectiveness of certain laws. The state's limited capacity to motivate participation from these corporations is what makes this reluctance a bigger challenge. This analysis highlights the necessity of strengthening political and legal frameworks to support more effective and productive collaborations between the university and industrial sectors. To bridge these gaps and improve the innovation ecosystem and drive socio-economic progress, this paper calls for a renewed approach to policymaking and legal reforms.